CORROSION INHIBITION OF X52 STEEL IN HIGH PRESSURE CARBON DIOXIDE (C02) ENVIRONMENT - MUSTAFA MUSA, ABDEL HAFIZ (2013)
Transport from the C02 source to the storage area is a key element in all carbon dioxide capture and sequestration systems, with pipelines being the logical and preferred transportation methods. Initial research indicates that a low-purity C02 poses a significant durability risk to oil and gas pipelines. If the water content of a C02 stream is above the solubility limit then a separate aqueous phase will exist. This aqueous phase can induce corrosion depending on its form and chemical composition. However, there exist a limited number of studies on the C02 corrosion inhibition of carbon steel transporting C02 saturated water in high pressure environment. The objective of this work is to elucidate the C02 corrosion inhibition effect of imidazoline and imidazoline added-thiosulfate as new inhibitors for X52 steel in C02 saturated water at different high pressures using electrochemical techniques such as linear polarization resistance (LPR), electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization sweep.